The Effect of Multimodal Non-pharmacological Interventions on Cognitive Function Improvement for People With Dementia: A Systematic Review - Sharew, Nigussie Tadesse (Frontiers in Public Health, 2022)
Word count: 221 Introduction: Dementia is a progressive brain degeneration characterized by a progressive deterioration in cognition and independent living capacity. Since dementia is a complex syndrome, multimodal non-pharmacologic interventions (MNPIs) are highly recommended. Currently, there is little available evidence to describe the content, length and frequency of multimodal interventions for cognitive function improvement for people with dementia (PWD). Method: A comprehensive search was done in PubMed, EMBASE, CINAHL, Web of Science, and Medline international databases. The quality appraisal of the studies was done by Cochrane risk of bias assessment tools. Results: Nineteen controlled trial studies were included. Most of the included studies reported that MNPIs resulted in improvement, stability, or attenuation of decline in cognitive function of PWD. The reported effectiveness of MNPIs on cognitive function ranged from medium (0.29 cohen’s d) to large (2.02 cohen’s d) effect sizes. The median duration of intervention was 12 weeks for a one-hour session. Conclusion: This systematic review showed that MNPIs might improve people's cognitive functions for PWD. Physical exercise, music and cognitive interventions were used in the content of multimodal interventions in a majority of the studies. Therefore, high-quality randomized controlled trial studies (RCTs) with repeated-measured design on the combined effect of physical exercise, music and cognitive intervention on cognitive function for PWD are recommended.